The Quality of Obtaining Surgical Informed Consent for Cesarean Section in Public Hospitals of Iran - Shadi Sabetghadam; Sedighe Rezaie Chamani; Zahra Amirkhanzadeh Barandouzi; Sedigheh Sedigh Mobarakabadi; Yalda Donyaei Mobarrez (Guilan University of Medical Sciences, 2021)
Abstract: Introduction: Nowadays, about 50-65% of births in Iran occur by Cesarean Section (CS). Informed consent (IC) is one of the most important ethical, legal and professional requirements of a surgical procedure. Objectives: This study aims to assess the quality of obtaining surgical IC from women underwent CS in public hospitals of Iran. Materials and Methods: In this analytical study with cross-sectional design, 300 postpartum women who had CS referred to two public hospitals in Rasht, Iran were participated through stratified random sampling method in 2016. Data were collected using a two-part researcher-made questionnaire. Collected data were analyzed by using descriptive statistics, Kruskal-Wallis test, Mann-Whitney U test, and Spearman's correlation test. Results: The mean age of participants was 29.84 ± 5.9 years. The majority of them (45.3%) had education lower than high school. The overall mean score for the quality of obtained IC was 62.23±23.38, out of 150 points. Regarding its dimensions, quality of acquiring IC form (20.21±7.12, out of 40 points), provision of CS-related information (15.67±11.10, out of 45 points), voluntariness (7.53±6.95, out of 25), and the physician-patient relationship (18.81±8.87, out of 40 points) were perceived poor. Women's educational level had a significant correlation with the IC quality dimensions of voluntariness (P=0.0001) and physician-patient relationship (P=0.043). The number of deliveries (P=0.008), live births (P=0.031), and stillbirth (P=0.0001) had a significant correlation with acquiring the IC form. The voluntariness was significantly associated with the number of live births (P=0.023) and stillbirth (P=0.001). The physician-patient relationship dimension was significantly associated with the number of pregnancies (P=0.023) and abortions (P=0.0001). The overall quality of obtained IC was significantly correlated with the women' age (r= 0.162, P= 0.005). Conclusion: Most of women in Iran are not informed enough about the CS and its consequences. Health care providers should pay more attention to the women's characteristics when obtaining IC for the CS.  We recommend essential changes in the process of obtaining surgical IC for the CS in public hospitals of Iran. Obtaining IC during pregnancy may reduce unnecessary CSs.